Effect of Biscuits and Muffins Added with Cornlettes Powder on the Glycemic Responses of Healthy Individuals - Anis Jauharah, M. Z.; Daniel Robert, S; Wan Ishak, Wan Rosli (Scientific Research Publishing, 2014)
Dietary fibre content is a known factor that can affect the postprandial glycemic responses of a food and meal. Cornlettes vegetable which is rich in dietary fibre has been studied for its potential in lowering the peak glycemic responses of biscuits and muffins. Cornlettes was processed into powder and formulated into four formulations of selected bakery products. The glycemic responses produced by portions of the biscuits and muffins containing 25 g available carbohydrate were measured in 11 healthy volunteers. The incremental area under curve (AUC) of control biscuits was greater (81 ± 11 mmol × min/l) than cornlettes powder (CP) added biscuit (63 ± 12 mmol × min/l). Likewise, the AUC of control muffins was higher (88 ± 13 mmol × min/l) than CP-added muffins (74 ± 12 mmol × min/l). Control biscuits had an intermediate GI value of 61 while CP-added biscuits had a low GI value of 46. Both control and CP-added muffins recorded intermediate GI values (58 and 57, respectively). It is concluded that CP can be incorporated in selected bakery products as a potential ingredient to help lower the peak rise of postprandial glycemic responses.